Development of e-LKPD Based on STEM to Enhance Students' Critical Thinking Skills on Topic of Renewable Energy - Salsabilla, Aulia; Kaniawati, Ida; Liliawati, Winny (Department of Physics Education, Universitas Mataram, 2024)
The research aims to develop e-LKPD based on STEM on renewable energy material that can facilitate students in enhancing critical thinking skills. This e-LKPD was developed by using the Research and Development (R & D) method with the ADDIE development model which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The feasibility of STEM-based e-LKPD is measured through validation involving 3 lecturers and 3 physics subject teachers. The enhancement of students' critical thinking skills was measured through data collection involving 35 grade X students. Students' response to the developed e-LKPD was measured by using a student response questionnaire. Based on the analysis results, it can be concluded that: 1) e-LKPD based on STEM is feasible to use when reviewed based on aspects of material/content, design, and language. 2) The enhancement of students' critical thinking skills obtained an N-Gain of 0.68 which means that learning using e-LKPD based on STEM can enhance students' critical thinking skills with a medium category. 3) STEM-based e-LKPDs received positive responses from students and received scores with good qualifications.